2013
DOI: 10.1155/2013/624815
|View full text |Cite
|
Sign up to set email alerts
|

The Ehrlich Tumor Induces Pain-Like Behavior in Mice: A Novel Model of Cancer Pain for Pathophysiological Studies and Pharmacological Screening

Abstract: The Ehrlich tumor is a mammary adenocarcinoma of mice that can be developed in solid and ascitic forms depending on its administration in tissues or cavities, respectively. The present study investigates whether the subcutaneous plantar administration of the Ehrlich tumor cells induces pain-like behavior and initial pharmacological susceptibility characteristics. The Ehrlich tumor cells (1 × 104–107 cells) induced dose-dependent mechanical hyperalgesia (electronic version of the von Frey filaments), paw edema/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 35 publications
1
46
0
4
Order By: Relevance
“…The in vitro cell based cytotoxicity assay is a useful and reliable method to demonstrate the activity of chemotherapeutic drugs and also gives a prior knowledge of the efficacy of various agents before using in invivo [21].The Ehrlich Ascites tumor is a murine mammary adenocarcinoma which grows in mice by intra peritoneal passages. The ascitic form of the tumor is the chosen experimental model to evaluate the influence of various drugs on its proliferation and host interaction against the cancer cells [22].Hence we used the Ehrlich Ascites Tumor cells for in vitroexperiments. In order to assess the toxicity of the compounds and evaluate their base-line metabolic effects on the cell [23], the trypan blue dye exclusion method of testing the cytotoxicity of these novel drugs in vitroon murine mammary carcinoma (EAT) cells was done.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro cell based cytotoxicity assay is a useful and reliable method to demonstrate the activity of chemotherapeutic drugs and also gives a prior knowledge of the efficacy of various agents before using in invivo [21].The Ehrlich Ascites tumor is a murine mammary adenocarcinoma which grows in mice by intra peritoneal passages. The ascitic form of the tumor is the chosen experimental model to evaluate the influence of various drugs on its proliferation and host interaction against the cancer cells [22].Hence we used the Ehrlich Ascites Tumor cells for in vitroexperiments. In order to assess the toxicity of the compounds and evaluate their base-line metabolic effects on the cell [23], the trypan blue dye exclusion method of testing the cytotoxicity of these novel drugs in vitroon murine mammary carcinoma (EAT) cells was done.…”
Section: Discussionmentioning
confidence: 99%
“…Ehrlich tumor is a spontaneous murine mammary adenocarcinoma adapted to the ascitic form and inoculated in mice by serial intraperitoneal passages [9,10]. This tumor model is widely used in experimental cancer studies due to its versatility; it is able to adapt to an ascitic form when inoculated by the intraperitoneal route or a solid form when inoculated by the subcutaneous route [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The Ehrlich ascites tumor cells are spontaneous murine mammary adenocarcinoma (6) and develop in almost all strains of mice as a rapidly growing carcinoma with very aggressive behavior (7). This tumor has similar features with human tumors and is sensitive to chemotherapy (8).…”
Section: Introductionmentioning
confidence: 99%
“…This tumor has similar features with human tumors and is sensitive to chemotherapy (8). Different studies indicated the benefi cial use of Ehrlich's ascitic carcinoma (EAC) and solid tumor (EST) models as a valuable tool in exploring biological activities in cancer and evaluating the effect of several chemical compounds (7,9,10).…”
Section: Introductionmentioning
confidence: 99%